Suplementação e irrigação na recria de bovinos de corte mantidos em pastagem de estrela africana - Bones, Everton Robert (2021)
Cattle farming systems on pastures need productivity increases to become sustainable nowadays. With this, the use of technologies such as supplementation and irrigation are available options. Thus, the objective of this work was to evaluate the performance of beef cattle with two levels of protein-energetic supplementation of low intake on African Bermudagrass pasture, overseeded in winter with oat and ryegrass, with or without irrigation. The research was carried out at the Universidade Tecnológica Federal do Paraná- Dois Vizinhos Campus. The experimental area had approximately 36,000 m², and it was divided into 12 paddocks, with an average size of 3,000 m² each. We used 24 castrated Angus steers. The animals were 11 ± 1 months of age and had an initial average live weight (LW) of 220 ± 10 kg. The experimental design was completely randomized in a 2 x 2 factorial scheme, with three replicates. The treatments were: irrigated pasture with protein-energetic supplementation of 1 g/kg-1 LW (IR 1) or 3 g/kg-1 LW (IR 3) and non-irrigated pasture with supplementation of 1 g/kg-1 LW (NIR 1) or 3 g/kg-1 LW (NIR 3). The supplement was provided daily, and it was regulated according to the animals’ weight every fifteen days. We used the continuous grazing method with a variable stocking rate. The daily accumulation rate, botanical and structural composition, and chemical composition of the pasture were evaluated. The average daily gain, carrying capacity, live weight gain per hectare, and ingestive behavior were determined for the animal performance variables. Ash contents were high and neutral detergent fiber contents were low in the winter and spring for the irrigated system. The dry matter and acid detergent fiber contents were low in spring for the irrigated system. Irrigation promoted an increase in the daily accumulation rate in the winter, with a positive effect on the weight gain per area. The 3 g/kg-1 LW supplement provided greater carrying capacity for the winter (1,435 vs 1,653 kg LW) and spring (2,811 vs 3,022 kg LW), without any change in the summer. Irrigation increased the number of bites and chews of the animals in winter and summer, the number of steps and bites were lower with a higher level of supplementation. Irrigation increased productivity and improved the nutritional value of the pasture with higher animal production per area in the winter. Supplementation of 3 g/kg-1 LW increases production per area on African Bermudagrass pasture.